INTERNALISATION OF ISLAMIC RELIGIOUS EDUCATION VALUES IN SHAPING RELIGIOUS CHARACTER - Hirzulloh, Muhammad Faiq (TAZKIA JURNAL, 2024)
PKBM Bhakti Luhur Dolopo Madiun is a non-formal education institution that accepts students who are vulnerable to dropping out of school.They previously attended formal institutions but could not continue their education due to lack of motivation, school laziness, and negative behavior.In this context, it is necessary to build religious character through the internalization of Islamic Religious Education values.Data were collected through interview and observation techniques regarding the process of internalizing the value of Islamic Religious Education and its influence on the religious character of students who are included in the category of vulnerable children dropping out of school.Data analysis was conducted using descriptive qualitative analysis method, including data reduction, data display, and conclusion drawing/verification. Based on the results of data analysis, it was found that the process of internalizing the value of Islamic Religious Education is carried out through the stages of planning, implementation, and evaluation.The internalization stage: teachers assist students in instilling religious character values through religious activities and provide examples in everyday life.The evaluation stage is carried out to assess the religious character of students and motivate students not to drop out.